The Influencing Factors of Capital Structure on Corporate Performance: Evidence from Listed Manufacturing Companies - Lamatta, Armando Ogalde (Journal of Global Economy, Business and Finance, 2026)
The study aimed to investigate the determinants of capital structure in relation to the performance of publicly listed manufacturing companies in East African nations. Panel data analysis was employed to achieve the research objectives. Secondary data were collected from East African manufacturing firms listed on the stock exchange, including Tanzania Breweries Limited, Tanzania Cigarette Company, British and America Tobacco, and East Africa Breweries Limited, spanning the years 2012 to 2021. Data analysis techniques such as multiple regression and the Pearson correlation method were applied. The findings indicated that several factors, including liquidity, asset tangibility, and growth prospects, had a positive impact on financial leverage, while firm size negatively affected capital structure. Furthermore, the study revealed a positive association between equity capital and financial performance, contrasting with the negative relationship between debt capital and financial performance. In conclusion, the study demonstrated that growth opportunities, liquidity, and asset tangibility significantly influenced capital structure in the context of financial performance. Conversely, debt capital exerted a detrimental effect on a firm's financial performance, while equity capital had a positive influence.